2010
DOI: 10.1186/1478-7954-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for enhancing public health utility of national causes-of-death data

Abstract: BackgroundCoverage and quality of cause-of-death (CoD) data varies across countries and time. Valid, reliable, and comparable assessments of trends in causes of death from even the best systems are limited by three problems: a) changes in the International Statistical Classification of Diseases and Related Health Problems (ICD) over time; b) the use of tabulation lists where substantial detail on causes of death is lost; and c) many deaths assigned to causes that cannot or should not be considered underlying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
356
0
52

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 357 publications
(414 citation statements)
references
References 25 publications
6
356
0
52
Order By: Relevance
“…When studying mortality trends for the five regions of Brazil during 15 years, it is important to keep in mind that coverage and quality of cause-of-death data varies across regions and time. Valid, reliable, and comparable assessments of trends in causes of death from even the best systems are limited by coverage and quality of data issues 16 . The first step of a mortality analysis consists in using traditional demographic tools for correction of coverage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When studying mortality trends for the five regions of Brazil during 15 years, it is important to keep in mind that coverage and quality of cause-of-death data varies across regions and time. Valid, reliable, and comparable assessments of trends in causes of death from even the best systems are limited by coverage and quality of data issues 16 . The first step of a mortality analysis consists in using traditional demographic tools for correction of coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of the sixth revision, the ICD-10 has been used not only to code deaths but also to cover all types of medical information, including non-fatal disorders and nonspecific medical conditions 16 . In this study, causes such as atherosclerosis and hypertension, more plausible as risk factors than underlying cause of death, were redistributed to cerebrovascular and other cardiovascular diseases, according to preconized methods 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology recommends that certain codes from the International Classification of Diseases (ICD) should not be considered as an underlying cause of death as they do not characterize this cause sufficiently to enable adequate public health interventions. These codes are named garbage codes, and considering that the burden of disease is estimated according to specific causes, these codes are redistributed 14 . Among more than 4,000 codes in the ICD-10 are considered to be garbage in the GBD 2015 study, the following were registered at a higher proportion in the SIM, in 2015, for children under 5 years of age: J18.0-J18.9-Unspecified pneumonia (n = 1,452), R00-R99-III-defined causes of death (n = 1,120), and A40.0-A41.9-Septicaemias (n = 779).…”
Section: Methodsmentioning
confidence: 99%
“…However, studies have indicated a tendency in considering other ill-defined causes and incomplete diagnoses from other chapters of ICD-10, defined in conjunction with those in Chapter XVIII as garbage codes (GCs). Despite still undeserving attention by health services and professionals, the importance of this group of causes has been highlighted in order to advance the discussion on the quality of the information 5,6 . The definition of GC was introduced in the Global Burden of Disease Study 1990, published in 1996 7 .…”
Section: Introductionmentioning
confidence: 99%